An Inspirited Artistic Co-Inquiry with Raw Energy - St. Georges, Darlene; Bickel, Barbara (Art/Research International, 2022)
This is the first article of an in-process, creation-centred research project exploring raw energy through the authors’ distinctive and complementary inquiry practices of creation-centred research (St. Georges, 2020, in press) and spontaneous creation-making (Bickel, 2020; Bickel & Fisher, 1993). Raw energy, as conceived, is experienced as spirit-in-motion in a process of manifestation—of making the invisible visible—and is rooted in an intra)inter-relational aesthetic. This creation-centred inquiry is a relational and animated approach to creating, inquiry, learning, unlearning, and teaching. It resists the colonial lens by virtue of exploring inner subjective space, relinquishing colloquial aesthetic constraints, and enveloping a sacred space in which to restore, heal, and decolonize the imagination. Led by breath)spirit, touch, intuition, experiential and conversational exchanges, and compassionate relationships, creative lifeforce is activated to forge new ways of knowing—moving toward the extraordinary. This article engages with theoretical and explanatory text, visual and poetic storying, and interactive breath that invites the reader into this inquiring journey.